2006
DOI: 10.1002/acp.1169
|View full text |Cite
|
Sign up to set email alerts
|

The negative effect of cross-examination style questioning on children's accuracy: older children are not immune

Abstract: We present data suggesting that the negative effect of cross-examination style questioning on children's accuracy is not limited to young children. Using an identical paradigm to that used with 5-and 6-year-olds by Zajac and Hayne in 2003, we examined the effect of cross-examination style questioning on 9-and 10-year-olds' accounts of a prior staged event. Like younger children, 9-and 10-year-old children made frequent changes to their original responses during cross-examination style questioning. Although 9-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
91
4
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(110 citation statements)
references
References 33 publications
14
91
4
1
Order By: Relevance
“…Overall, cross-examination-style questioning significantly decreased the accuracy of children's reports, to a point where accuracy scores during the cross-examination interview did not differ significantly from 50%. Similar findings have since been obtained in a sample of older children (9-and 10-year-olds; Zajac & Hayne, 2006), when the delay between the memory event and cross-examination is decreased (Righarts, Zajac, & Hayne, 2008), and using a more conservative scheme to code changes to earlier testimony (Righarts et al, 2008).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Overall, cross-examination-style questioning significantly decreased the accuracy of children's reports, to a point where accuracy scores during the cross-examination interview did not differ significantly from 50%. Similar findings have since been obtained in a sample of older children (9-and 10-year-olds; Zajac & Hayne, 2006), when the delay between the memory event and cross-examination is decreased (Righarts, Zajac, & Hayne, 2008), and using a more conservative scheme to code changes to earlier testimony (Righarts et al, 2008).…”
supporting
confidence: 68%
“…Recent laboratory research has suggested that cross-examination of children does not reliably uncover the truth. In fact, when interviewed using crossexamination-style questions, children frequently make changes directed away from the truth, resulting in dramatically decreased accuracy levels (Righarts et al, 2008;, 2006.…”
Section: Implications For Further Researchmentioning
confidence: 99%
“…Moreover, cross-examination, which is typically a particularly anxietyprovoking forum for answering questions, reduces the accuracy of children's testimony (Zajac & Hayne, 2003, 2006. Children's negative feelings about answering questions in the courtroom might be decreased by programs developed to help children navigate the legal process (Nathanson, 2014).…”
Section: Children's Feelings About Answering Questions In Courtmentioning
confidence: 98%
“…This is because they often change answers in response to cross-examination -both their correct and their incorrect direct examination answers (Zajac & Hayne, 2003;Zajac, Jury, & O'Neill, 2009). In fact, preschoolers, older children and adults are vulnerable to the deleterious impact of crossexamination (Zajac & Hayne, 2006;Zajac & Cannan, 2009) -highlighting the fact that social pressures can undermine accurate memory reporting. Providing support persons for child witnesses and preparation for legal participation are procedures meant to alleviate some of the stresses of testifying for children and seem to offer some benefits (Malloy et al, 2007).…”
Section: Communication and Linguistic Abilitymentioning
confidence: 99%